(untitled) (Web of Teachers: Inderscience Research, 2026)
This article analyzes the manifestation of the idea of ecological modernization in the Jadid thought formed at the beginning of the 20th century. The study was conducted on the basis of historical-comparative and discursive methods. Although the Jadid intellectuals did not use the term ecology, they interpreted the issues of land, water, landscaping, modernization of agriculture, sanitation and the development of urban culture as an important factor of national development. The results of the analysis showed that environmental modernization in the Jadid thought was inextricably linked with social and economic reforms.